One-step synthesis of bovine serum albumin nanoparticles by hydrothermal green treatment - Esfahan, Zahra Maghareh; Shamsul Izhar; Izadiyan, Zahra; Toozandejani, Meysam; Yoshida, Hiroyuki (Jihad Danishgahi,Iranian Research Center for Chemical Industries, 2022)
The non-toxic BSA-based nanoparticles (NPs) are developed without any additives with hydrothermal subcritical water treatment (SCWT). The optimum BSA-based NPs are gained by applying Response Surface Methodology (RSM) based on particle size, zeta potential, and polydispersity. The SCWT conditions are optimized in terms of these three dependent variables, which have significant impacts on the BSA-based NPs application. The optimum BSA-based NPs prepared with 2.73% (w/v) of initial BSA solution concentration, the lowest initial concentration that use to synthesis BSA-based NPs by now. The SCWT condition of 173 oC and 2.07 min of SCWT holding time shows that the zeta potential of -38.87 mV with the finest particle size and PI (147.32 nm and 0.24, respectively) is the optimized composition. The fabricated BSA-based NPs are characterized by the UV-vis, screening electron microscope (SEM), and stability assessment study.